Power, politics, and political skill in job stress - Rosen, Christopher C.; Perrewe, Pamela L. (Emerald Publishing Limited, 2017)
The objective of this series is to promote theory and research in the increasingly growing area of occupational stress, health and well being, and in the process, to bring together and showcase the work of the best researchers and theorists who contribute to this area. As you know, questions of work stress span many disciplines and many specialized journals. Our goal is to provide a multidisciplinary and international collection that gives a thorough and critical assessment of knowledge, and major gaps in knowledge, on occupational stress and well being. Research in Occupational Stress and Well Being is focused on power, politics and influence. It has been widely accepted that power, politics and influence are pervasive within most social entities, including work organizations. However, research on the role of social influence in the stress process is still needed. This volume will focus on the connections between social influence processes, broadly defined (e.g., power, politics, political skill and influence), and employee stress, health, and well-being.
Prelims -- All roads lead to well-being: unexpected relationships between organizational politics perceptions, employee engagement, and worker well-being -- Positive politics, negative politics, and engagement: psychological safety, meaningfulness, and availability as "black box" explanatory mechanisms -- Stress, psychological strain, and reduced organizational effectiveness: the destructive consequences of the use of intimidation and pressure by supervisors -- Sensitivity and adaptability in the face of powerlessness: the roles of political will and political skill within the experience of powerlessness and its impact on stress-related outcomes -- Organizational change, uncertainty, and employee stress: sensemaking interpretations of work environments and the experience of politics and stress -- Puppet or puppeteer? the role of resource control in the occupational stress process -- About the authors -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Quality of work life; Industrial sociology; Well-being.; Health & Fitness, Work-Related Health; Occupational & industrial psychology